Prevalence of Cognitive Impairment No Dementia in a Rural Area of Northern China - Zhang, Ying (2014)
OBJECTIVE: Few data are available on the prevalence of cognitive impairment no dementia (CIND) in rural China. The aim of this study was to estimate the prevalence of CIND in individuals aged 60 years and older in a large rural community, and to analyze the associated risk factors. METHODS: A two-phase, door-to-door epidemiological study was used for residents aged 60 years and older in Ji County, a rural county near Tianjin in Northern China. In phase 1 of the study, the Mini-Mental State Examination and Clinical Dementia Rating were administered for screening purposes. In phase 2, the subjects who screened positive were further examined by neurologists. A total of 5,744 individuals underwent the home visit interview, where demographic variables and comorbidities were recorded; 5,550 individuals completed the two phases. CIND was diagnosed by the Aging, Demographics and Memory Study on CIND criteria. The odds ratio (OR) for each risk factor was calculated by logistic regression analysis. RESULTS: The prevalence of CIND among those aged 60 years and older was 23.3%. The prevalence of CIND was lower among those with a higher level of education or social involvement. CIND was more prevalent in fe males, older individuals, those with a past history of stroke, and those living without a partner. Significant risk factors were found by multivariate analyses: past history of stroke (OR = 1.889; 95% CI: 1.437–2.483); being female (OR = 1.546; 95% CI: 1.305–1.832); and having no partner (divorced, widowed or single; OR = 1.250; 95% CI: 1.042–1.499). In turn, level of education (OR = 0.560; 95% CI: 0.460–0.681) and engagement in social activities (OR = 0.339; 95% CI: 0.258–0.404) were protective factors. CONCLUSIONS: This is the first large-scale community-based epidemiological study assessing the prevalence of cognitive loss in the rural Chinese population. The total prevalence of CIND observed was 23.3%, which was higher than in other studies in Western and Asian countries. Living without a partner, female gender and previous stroke increased the risk of CIND, whereas a higher level of education and engagement in social activities reduced the risk of CIND.